Comercialización del cultivo de naranja (Citrus sinensis, L) en el Ecuador - Suarez Piña, Merly Isabel (2023)
The Orange had its origin in Southeast Asia, it has been cultivated and consumed for many years, this crop has become a fundamental support for the country's economy, because the climatic and topographic conditions are optimal and have made it easier to plant these plants and thus expand this crop, both for national and international consumption. The objectives of the research are to analyze the marketing of oranges in Ecuador, as well as to understand the process that producers carry out to market their products. Additionally, determine the socioeconomic importance that this crop represents for producers. The present investigation gave results that more than 80% of orange producers market their product by the thousand, since they consider it to be more profitable and they obtain good income. 15% of producers prefer to sell by lot. In the marketing of oranges, producers do so indirectly, since intermediaries have more participation in the entire marketing process. The actors involved in the marketing process are the producer, collector, retailers and final consumers, all of whom play a fundamental role within the chain. To prepare the document, information was collected from magazines, current documents, websites and scientific articles, which intervened in the contribution of opinions and ideas of authors that allowed analyzing the development of this research. Relevant topics were specified regarding the analysis of the commercialization of orange cultivation in Ecuador.